Уповноважений Верховної ради України з прав людини та національні судові інституції: питання функціональної взаємодії - Волкова Дарія Євгенівна; Волкова Дарья Евгеньевна; Volkova Dariya (My University, 2011)
In the article in the context of the constitutionally conditioned principle of co-operation of branches of state power the questions of functional interoperability of the authorized Agent of Verkhovna Rada of Ukraine and institutes of department judicial of Ukraine are examined in the field of providing of human rights.
Волкова Д. Є. Уповноважений Верховної ради України з прав людини та національні судові інституції: питання функціональної взаємодії / Д. Є.Волкова // Актуальні проблеми держави і права : зб. наук. пр. /редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2011. – Вип. 61. – С. 107-117.
Keywords: принцип функціональної взаємодії; права людини; Уповноважений Верховної Ради України з прав людини; суди України; принцип функционального взаимодействия; права человека; Уполномоченный Верховной Рады Украины по правам человека; суды Украины; principle of interoperability; human rights; Ukrainian Parliament Commissioner for Human Rights; Ukrainian courts